2019
DOI: 10.1002/jcb.29286
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated expression of STAT1, miR‐150, and miR‐223 in peripheral blood mononuclear cells of coronary artery disease patients with significant or insignificant stenosis

Abstract: Coronary artery disease (CAD) is a multicellular disease characterized by chronic inflammation. Peripheral blood-mononuclear cells (PBMCs), as a critical component of immune system, actively cross-talk with pathophysiological conditions induced by endothelial cell injury, reflecting in perturbed PBMC expression. STAT1 is believed to be relevant to CAD pathogenesis through regulating key inflammatory processes and modulating STAT1 expression play key roles in fine-tuning CAD-related inflammatory processes. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Previous high-throughput sequencing data showed that gga-miR-223 was signally down-regulated in MG-infected chicken embryo lung [37]. Importantly, accumulating data has suggested that miR-223 plays an important role in various diseases, especially respiratory disease [20,38,39]. MiR-223 plays a key role in regulating the immune in ammatory response to neutrophil asthma by inhibiting the NLRP3/ IL-1β [40]; pharmacological blockade of the miR-223-NLRP3-IL-1β signaling axis alleviates acute respiratory distress syndrome [41].…”
Section: Discussionmentioning
confidence: 99%
“…Previous high-throughput sequencing data showed that gga-miR-223 was signally down-regulated in MG-infected chicken embryo lung [37]. Importantly, accumulating data has suggested that miR-223 plays an important role in various diseases, especially respiratory disease [20,38,39]. MiR-223 plays a key role in regulating the immune in ammatory response to neutrophil asthma by inhibiting the NLRP3/ IL-1β [40]; pharmacological blockade of the miR-223-NLRP3-IL-1β signaling axis alleviates acute respiratory distress syndrome [41].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a 260/280 ratio of 2.0 and 260/230 in the range of 2.0–2.2 was chosen as pure for RNA. For integrity evaluation of the samples, we used %1.5 agarose gel electrophoresis (Rodrigues & de Brito Neto, 2017; Saadatian et al., 2019). Total RNA (> 500 ng) was converted to cDNA using the cDNA Synthesis Kit (Cat No: YT4500; Yekta Tajhiz Azma®, Iran).…”
Section: Methodsmentioning
confidence: 99%
“…More researches are needed to confirm the role of miR-223-3p as a diagnostic or predictive biomarker of myocardial infarction. Furthermore, the expression of miR-223-3p in peripheral blood mononuclear cells was downregulated in patients who were diagnosed as coronary artery disease with significant or insignificant stenosis compared with healthy controls, which was most prominent in patients with insignificant stenosis, indicating that miR-223-3p in peripheral blood mononuclear cells might be positively related to severity of coronary artery disease and could be used for discriminate patients with significant or insignificant stenosis (115).…”
Section: Role Of Mir-223-3p In Diagnosis Severity Assessment and Rimentioning
confidence: 98%